2021
DOI: 10.3390/ijms22042088
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase (PI3K) Reactive Oxygen Species (ROS)-Activated Prodrug in Combination with Anthracycline Impairs PI3K Signaling, Increases DNA Damage Response and Reduces Breast Cancer Cell Growth

Abstract: RIDR-PI-103 is a novel reactive oxygen species (ROS)-induced drug release prodrug with a self-cyclizing moiety linked to a pan-PI3K inhibitor (PI-103). Under high ROS, PI-103 is released in a controlled manner to inhibit PI3K. The efficacy and bioavailability of RIDR-PI-103 in breast cancer remains unexplored. Cell viability of RIDR-PI-103 was assessed on breast cancer cells (MDA-MB-231, MDA-MB-361 and MDA-MB-453), non-tumorigenic MCF10A and fibroblasts. Matrigel colony formation, cell proliferation and migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…In breast cancer cells RIDR-PI-103 in combination with doxorubicin inhibited cell proliferation, impaired PI3K signaling, and activated DNA damage [30]. Use of RIDR-PI-103 in cord blood cells and fibroblasts did not demonstrate toxicity [29,30]. Similarly in our study, we observed that RIDR-PI-103 had increased specificity in TDR cells over melanocytes at 5 µM (Figs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In breast cancer cells RIDR-PI-103 in combination with doxorubicin inhibited cell proliferation, impaired PI3K signaling, and activated DNA damage [30]. Use of RIDR-PI-103 in cord blood cells and fibroblasts did not demonstrate toxicity [29,30]. Similarly in our study, we observed that RIDR-PI-103 had increased specificity in TDR cells over melanocytes at 5 µM (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…A boron-containing bioisostere of PI-103 offered improved bioavailability [28]. ROS-induced drug release (RIDR)-PI-103 is a prodrug of PI-103, which in presence of high ROS releases the biologically active component, PI-103 [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…According to this theory, the high ROS production in cancer cells causes malfunction of the mitochondrial membrane, inhibits the PI3K/Akt protein kinase, and leads to the Raf-1/ERK1/2 signaling pathway inhibition. Finally, apoptosis is induced, and cell survival, proliferation, and metastasis are arrested. , …”
Section: Resultsmentioning
confidence: 99%
“…Recently, great progress has been made in the understanding of ROS biology, and there is increasing evidence that the effects of ROS are gradient-dependent, with a threshold of habituation, which affects their signal transduction and toxicity induction function, thus resulting in either "good" or "bad" ROS (33). For example, ROS play a key role in the activation of tumor-promoting signaling pathways (64,66,67). Moreover, abnormal production of ROS and ineffective neutralization of excessive ROS levels can lead to tumor growth and progression through different signaling pathways, including phosphatidylinositol 3kinase/protein kinase inhibitor/mammalian target of rapamycin (PI3/Akt/mTOR), vascular endothelial growth factor (VEGF)/ VEGF receptor, phosphatase and tensin congeners (PTEN), and matrix metalloproteinase (MMP) pathways (68).…”
Section: Reactive Oxygen Species (Ros)-responsive Npsmentioning
confidence: 99%